Conformation controlled turn on–turn off phosphorescence in a metal-free biluminophore: thriving the paradox that exists for organic compounds. Issue 40 (29th September 2016) - Joshi, Ritika; Meitei, Oinam Romesh; Jadhao, Manojkumar; Kumar, Himank; Ghosh, Sujit Kumar
Abstract : The dual state intense emission, both fluorescence and phosphorescence, of CBIQD by way of conformational regulation–deregulation. Abstract : The legacy of phosphorescence from expensive organometallic compounds has inspired researchers to develop efficient metal-free organic phosphors. Although organic phosphors offer a cheaper alternative, the long-lived triplets of organic phosphors that are primarily consumed by vibrational dissipation need to be adequately suppressed, and this provides an opportunity to design new organic entities, at par with the organometallic compounds, based on conformational control and incorporation of useful functional groups to alter their emissive properties, especially phosphorescence. Here, we have achieved a proficient dual state emission, underlining the key design rule of conformational control in an organic molecular platform for 2-(6-chlorobenzo[ d ]thiazol-2-yl)-1 H -benzo[ de ]isoquinoline-1, 3(2 H )-dione (CBIQD). In contrast to other known naphthalimides, the system limiting access to non-radiative triplet states is achieved by steric encumbrance which exhibits strong phosphorescence. Here, in addition to strong fluorescence (from planar conformer), phosphorescence is unlocked by suppression of non-radiative channels from the non-planar conformer in glassy solvents (77 K) and when embedded in a polymer matrix of poly(methyl methacrylate) (PMMA) at RT. The spectroscopic delineation of adopted geometry and optical property relationship is sought by a steric approach, extent of intramolecular charge transfer (ICT), presence of carbonyl groups, directed heavy atom effect and the spin–orbit coupling (SOC) invoked by –S– and –Cl atoms. Time dependent density functional theory (TD-DFT) is used to explain the favourable mechanistic path for the decay of excited states (ESs) leading to phosphorescence from a non-planar conformer and fluorescence from a planar conformer. The spectacular access to the radiative singlet and triplet states suggests that there is less scope for loss channels. The phosphorescence of the CBIQD–PMMA system may find use in other biomedical applications due to the biocompatibility of each component.